2018
DOI: 10.1186/s13014-018-0983-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after PSMA PET/CT based radiotherapy in patients with biochemical persistence or recurrence after radical prostatectomy

Abstract: BackgroundPSMA PET/CT visualises prostate cancer residual disease or recurrence at lower PSA levels compared to conventional imaging and results in a change of treatment in a remarkable high number of patients. Radiotherapy with dose escalation to the former prostate bed has been associated with improved biochemical recurrence-free survival. Thus, it can be hypothesised that PSMA PET/CT-based radiotherapy might improve the prognosis of these patients.MethodsOne hundred twenty-nine patients underwent PSMA PET/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 40 publications
0
42
1
Order By: Relevance
“…On the other hand, matching for these risk factors reduced the impact of the post-RP PSA level. An association of adverse clinicopathological parameters with the post-RP PSA level has been reported in several recent studies, in one instance even with the PSA threshold at 0.01 ng/mL [8,[15][16][17].…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, matching for these risk factors reduced the impact of the post-RP PSA level. An association of adverse clinicopathological parameters with the post-RP PSA level has been reported in several recent studies, in one instance even with the PSA threshold at 0.01 ng/mL [8,[15][16][17].…”
Section: Discussionmentioning
confidence: 74%
“…A change in RT target planning or management was described in 50%-77% of all patients using 68 Ga-PSMA-11 PET/CT (32)(33)(34). In addition, it has been shown that a 68 Ga-PSMA-11 PET/CT-based RT target leads to a significant PSA response in patients with BR (5,6). In our cohort, 68 Ga-PSMA-11 PET/MRIpositive lesions outside a standard RT target volume were found in more than 70% of all patients with PSMA-positive lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent metaanalysis demonstrated a detection rate of 45% (95% confidence interval [CI], 39%-52%) using the new 68 Ga-labeled PET tracer targeting the prostate-specific membrane antigen (PSMA) in patients with BR and PSA values of 0.2-0.49 ng/mL (4). PSMA-based targeted radiotherapy (RT) might therefore become an option in patients with BR (5,6). However, data about the oncologic outcome of PSMA-based targeted RT is still limited, and ongoing clinical trials have to be completed before definitive conclusions on the effect of targeted salvage treatments can be drawn (7).…”
mentioning
confidence: 99%
“…A few studies have already shown the high impact and good response of PSMA-based therapy on outcome (51)(52)(53). However, limitations such as small samples of patients, exclusion of those with metastatic disease, and short-term follow-up might account for nonidentical categories of data.…”
Section: Discussionmentioning
confidence: 99%